The main factor of education is information and communication technologies - Boztai Зәмзәгүл (Рroblems of engineering and professional education, 2023)
The article reveals the concept of "information society" and its place in the education system based on modern computer technologies. The active use of information and communication technologies (IiICT) in education allows not only to take a fresh look at the pedagogical process, but also provides the necessary scientific and methodological apparatus for their analysis and updating, and the computerization of the learning process is one of the main factors in the content of education.